2021
DOI: 10.1111/ppa.13414
|View full text |Cite
|
Sign up to set email alerts
|

Reservoirs of plant virus disease: Occurrence of wheat dwarf virus and barley/cereal yellow dwarf viruses in Sweden

Abstract: Non-crop plants such as grasses and volunteer plants are an inseparable part of the flora of crop fields, and can influence virus incidence in crop plants. The presence of grasses as virus reservoirs can lead to a higher probability of virus incidence in crop plants. However, the role of reservoirs as an inoculum source in agricultural fields has not been well studied for many viral diseases of crops. Grasses have been found to constitute potential reservoirs for cereal-infecting viruses in different parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…This experiment clearly exemplifies that climate change may lead to the rapid appearance of adapted fungal pathogens, with conserved capacities to infect different hosts species. It also highlights the importance of wild species as reservoirs for crop diseases ( Parker and Gilbert, 2004 ; Awasthi et al., 2015 ; Yazdkhasti et al., 2021 ). Christen and French (1982) found that a range of V. alfalfae strains ( V. albo-atrum isolated from alfalfa) from western Canada and north-western USA had an optimal temperature in culture of 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment clearly exemplifies that climate change may lead to the rapid appearance of adapted fungal pathogens, with conserved capacities to infect different hosts species. It also highlights the importance of wild species as reservoirs for crop diseases ( Parker and Gilbert, 2004 ; Awasthi et al., 2015 ; Yazdkhasti et al., 2021 ). Christen and French (1982) found that a range of V. alfalfae strains ( V. albo-atrum isolated from alfalfa) from western Canada and north-western USA had an optimal temperature in culture of 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…WDV has a wide range of monocotyledonous hosts, including economically important cereals such as wheat, barley, oat, rye and triticale and some wild grasses (Vacke 1972 ). The main virus sources are infected field stands and self-sown ‘volunteer’ cereal plants in lay fields (Manurung et al 2004 ; Mehner et al 2003 ), while infected wild grasses are less important but may act as long-term reservoir for the virus (Ramsell et al 2008 ; Yazdkhasti et al 2021 ). Primary infection of winter wheat occurs in autumn when infected adult leafhoppers transfer the virus into newly sown crops.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wild A. cordata was identified as the natural reservoir of GVCV because the virus was detected in 31% of wild A. cordata , which showed mild vein clearing, and it could be transferred between A. cordata and grape by aphids (Petersen et al, 2019). Wheat dwarf virus (WDV) can be transmitted from its infected reservoir, ryegrass, which has a very low titer of WDV, to wheat by leafhoppers (Yazdkhasti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To identify the natural reservoir of a crop‐infecting virus, surveys are conducted to collect all weeds, volunteer plants, and potential reservoirs growing in and around crop fields (Ling et al, 2011; Mueller et al, 2012; Yazdkhasti et al, 2021). Viral infections in these samples are diagnosed with serological tests (e.g., enzyme‐linked immunosorbent assay [ELISA]) and molecular tests such as PCR or qRT‐PCR (Yazdkhasti et al, 2021). Finally, a transmission experiment was conducted to determine whether the virus can be transmitted between reservoir and host plants (Figure 2).…”
Section: Introductionmentioning
confidence: 99%